Cities and health: an evolving global conversation. Issue 1 (2nd January 2017) - Grant, Marcus; Brown, Caroline; Caiaffa, Waleska T.; Capon, Anthony; Corburn, Jason; Coutts, Chris; Crespo, Carlos J.; Ellis, Geraint; Ferguson, George; Fudge, Colin; Hancock, Trevor; Lawrence, Roderick J.; et al.
Abstract: The Cities and Health journal sees its launch in 2017. Looking back over half a century of growth and global expansion in economic activity, although there have been societal benefits, negative impacts are starting to take their toll on planetary resources and human health. As we enter what is being termed The Anthropocene, the city is becoming the preferred habitat for humanity. The imprint of city lifestyles, in terms of both resource use and waste, is found across the globe, threatening the ecosystem services that support our health. In cities themselves, due to risks and challenges to health, we are witnessing a rise in non-communicable disease, twinned with infectious disease for the many who live increasingly in informal or slum urban development. High levels of health inequity are found within urban populations. The resultant health problems are placing increasing strain on health services, with pressure only set to increase due to continuing urbanization and ageing populations. Evidence increasingly demonstrates that many aspects of city and neighbourhood form, urban and transport design, and residential environments play an important role in mediating health and health equity outcomes. The new journal Cities & Health is being launched to support political, academic and technical leadership and transdisciplinarity in this field. For this endeavour we will need to re-examine the nature of evidence required before we act; to explore how academics, policy-makers, practitioners and communities can best collaborate using the city as a laboratory for change; and to develop capacity building for healthier place-making at professional and community levels.